Communication—Detection of Salivary Cortisol Using Zinc Oxide and Copper Porphyrin Composite Using Electrodeposition and Plasma-Assisted Deposition. (31st July 2020) - Sonawane, Apurva; Nasim, Sana; Shah, Pratik; Ramaswamy, Sharan; Urizar, Guido; Manickam, Pandiaraj; Mujawar, Mubarak; Bhansali, Shekhar
Abstract : The reliability of two novel cortisol sensors was evaluated by detecting variations in salivary cortisol levels of college students. The diurnal salivary cortisol fluctuations in 50 college students were monitored, and the sensor results were compared with commercial immunoassays. The chemical sensors were prepared using two different methodologies; electrodeposition and cold atmospheric plasma deposition. The comparison between these two methods shows the potential of proposed methods over conventional cortisol assays. The sensitivity of plasma deposited cortisol sensor increased from 0.918 to 3.04 μ A/( μ g dl −1 ). Sensors fabricated using the plasma technique showed repeatability and provided a direct readout with a faster response.